FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN NON KEUANGAN YANG TERDAPAT DI BURSA EFEK INDONESIA - Deasy Putri; Suryanto (E-Jurnal Akuntansi TSM, 2022)
This study aims to examine the factors that affect the value of companies in non-financial companies in Indonesia. There are seven independent variables in this study, including: dividend policy, managerial ownership investment opportunity, leverage, profitability, firm size, earnings per share.Fifty eight companies listed during the period 2014-2016 in Indonesia were selected as samples using purposive sampling method. And data analysis is done by using multiple linear regression method.The results of this study indicate that there is a positive effect of dividend policy, profitability, company size, earnings per share on the value of the company. While investment opportunity, managerial ownership, and leverage have no effect on company value.